A New Era of Education: Incorporating Machine Teachers Into Education - Jihyun Kim (Central States Communication Association, 2021)
This editorial briefly discusses the potential of machine agents in education that can assist in creating more positive and meaningful teaching and learning environments. Then, it introduces three articles, two empirical research studies and one research-based instructional activity, compromising a special section on "Machine Teachers in Education" of Journal of Communication Pedagogy. Collectively, these articles help us better understand the role of machines in education and facilitate intellectual dialogues.